2012
DOI: 10.1021/jp2097636
|View full text |Cite
|
Sign up to set email alerts
|

About the Nitrogen Location in Nanocrystalline N-Doped TiO2: Combined DFT and EXAFS Approach

Abstract: N-doped titanium dioxide is one of the most promising materials for photocatalysis in the visible region. The exact location of nitrogen in the host lattice is still under debate. Here, we synthesized a series of N-doped titania nanoparticles. Average Ti nearest neighbors distances were obtained from EXAFS experiments and compared with DFT calculations at different levels of theory. The comparison shows that N substitutes oxygen at low levels of doping, whereas oxygen vacancy creation is observed at higher dop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

13
77
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 79 publications
(90 citation statements)
references
References 54 publications
(45 reference statements)
13
77
0
Order By: Relevance
“…Therefore, the reduction of TiO 2 takes place at 550 C. This onset temperature is consistent with the decomposition temperature of NH 3 and therefore, the reduction and subsequent N incorporation are indeed caused by atomic H generated by decomposition of NH 3 36. The present results are supported by theoretical prediction showing that the introduction of V O stabilizes the formation of N s [37][38][39].…”
supporting
confidence: 86%
“…Therefore, the reduction of TiO 2 takes place at 550 C. This onset temperature is consistent with the decomposition temperature of NH 3 and therefore, the reduction and subsequent N incorporation are indeed caused by atomic H generated by decomposition of NH 3 36. The present results are supported by theoretical prediction showing that the introduction of V O stabilizes the formation of N s [37][38][39].…”
supporting
confidence: 86%
“…The Horae suite of programs 41 , based on the IFEFFIT library 42 , was used throughout data processing and fitting. The same multi-step fitting strategy described in detail elsewhere 43 was applied to extract information on the average coordination geometry around Ti. As for the spectra at the Nb K-edge, we considered as negligible the amount of dopant possibly present in the minority phase of brookite with respect to the major anatase one.…”
Section: Extended X-ray Absorption Fine Structure (Exafs)mentioning
confidence: 99%
“…They discovered that the N-doping was responsible for the oxygen-vacancies formation in titanium dioxide. In a more recent investigation supported by DFT calculations and EXAFS, Ceotto et al postulated that nitrogen preferentially occupies the axial position in the TiO 6 polyhedra replacing the lattice oxygen at low doping levels and forming oxygen-vacancies at high dopant concentrations 31 . Several years later, Sahoo et al found out by means of EXAFS that the nitrogen interstitial doping is responsible for the reduction of Ti-O coordination number and the increase of the axial and equatorial Ti-O bond lengths 32 .…”
mentioning
confidence: 99%